Design of tapered slot vivaldi fuitenna array using FR4 substrate article / Muhamad Ridzuan Mohamad Ibrahim - Mohamad Ibrahim, Muhamad Ridzuan
This dcgree thesis discuss the performance and behavior of ViveHi lntennl array for the ultra-wideband (UWB) ftequency ranges, The design construction and characterization of the Vivaldi antenna by using two (2) diftrent dcsEn but sane array whicb is I x 2 arrays. The dilference is the design of tepered slot wide end where thewkle end of the tepercd slot of the lirst design GSAf) was to mest one rnother and aiother design (TSA2) ls by edding space between widc end of the array. Then these antennas werc constructed using trR4 substrrtes by using CST micnoweve softrvarc. The Vivaldi enlenne produced that cen be operated et X-hnd and using substrate that available and cheap